2006
DOI: 10.1161/01.atv.0000196565.38679.6d
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Vasa Vasorum Neovascularization and Plaque Progression in Aortas of Apolipoprotein E −/− /Low-Density Lipoprotein −/− Double Knockout Mice

Abstract: Objective-We hypothesized that apolipoprotein E (apoE)Ϫ/Ϫ /low-density lipoprotein (LDL) Ϫ/Ϫ double knockout mice might develop vasa vasorum (VV) in association with advanced lesion formation. Methods and Results-Aortas from apoEϪ/Ϫ /LDL Ϫ/Ϫ mice aged 16, 18, 20, or 80 weeks were infused in situ with Microfil, harvested, and scanned with micro-computed tomography (CT). We characterized plaque volume and CT "density" as well as VV luminal volume along the aorta using Analyze 6.0 software. Results were complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 36 publications
3
85
0
Order By: Relevance
“…An acquisition time at 20 to 30 minutes after contrast agent administration could be optimal, because after this time a nonspecific plaque accumulation may occur, as suggested by the control contrast agent, USPIO-PEG. This could be driven by the enhanced permeability and retention (EPR) effect in areas with leaky vasculature (ie, hypervascularity, enhanced permeability, and low washout), 28 the same as in tumors. The contrast related to the EPR effect is illustrated by USPIO-PEG, which is responsible for 70% of the specific plaque enhancement at very late imaging times after administration (ie, 221 minutes); 32 minutes after administration, the plaque contrast produced by USPIO-PEG was as low as 20% of the maximum enhancement attained with USPIO-R832 and USPIO-R826.…”
Section: In Vivo Behavior Of Functionalized Uspio Derivatives and Permentioning
confidence: 99%
“…An acquisition time at 20 to 30 minutes after contrast agent administration could be optimal, because after this time a nonspecific plaque accumulation may occur, as suggested by the control contrast agent, USPIO-PEG. This could be driven by the enhanced permeability and retention (EPR) effect in areas with leaky vasculature (ie, hypervascularity, enhanced permeability, and low washout), 28 the same as in tumors. The contrast related to the EPR effect is illustrated by USPIO-PEG, which is responsible for 70% of the specific plaque enhancement at very late imaging times after administration (ie, 221 minutes); 32 minutes after administration, the plaque contrast produced by USPIO-PEG was as low as 20% of the maximum enhancement attained with USPIO-R832 and USPIO-R826.…”
Section: In Vivo Behavior Of Functionalized Uspio Derivatives and Permentioning
confidence: 99%
“…Multiple studies have demonstrated the importance of VV neovascularization in the development of atherosclerosis (2,18,22,31,32,42,44), and VEGF-induced neovascularization has been postulated to be a therapeutic target to reduce atherosclerosis (21,43). An interesting finding from our experiments is that VEGF-induced neovascularization was present despite hypoactivation of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that vasa vasorum neovascularization increases in both early and advanced AS [5][6][7] . Vasa vasorum neovascularization is also strongly associated with inflammatory infiltration, lipid deposition, intraplaque hemorrhage, and hemosiderin deposit [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 93%